OPTIMIZING PHYSICAL TRAINING IN JUNIOR FEMALE BASKETBALL PLAYERS (University Arena, 2025)
Women's basketball has come a long way recently. Many clubs have sprung up, the number of competitions has increased and girls have started practicing and playing basketball from a very young age. In the last twenty years we have raised several generations of basketball players, generations that have won numerous national titles for CSS, but we always knew that we still had some work to do in terms of physical training. So, with the generation of girls born in 2002, we planned a training program to improve and develop physical preparation. The experiment was conducted with 14–16 year old female basketball players over a period of one year, including two final tournaments. The study was conducted in two stages: the first test was conducted in the competitive period before the U14 final tournament (February 2023), where the team lost the gold medal, and the second test was also conducted in the competitive period before the U15 final tournament (February 2024), where the team won the gold medal. Tests were conducted on 8 indicators, which provide information about the basic parameters of the preparation of the tested basketball athletes. In order to achieve the set objectives and tasks of the present study, we applied the following research methods: literature review, four anthropometric tests and 4 specific physical tests. Along with the regular basketball training, we introduced specific physical conditioning training twice a week for 6 months. Results obtained from the tests were processed, variances were analyzed, followed by a correlation analysis. The analysis of the results from the two tests established that the applied specific fitness training program had a positive impact on the basketball players' fitness, which is why we will continue to implement it further in the training process and will probably conduct a third test before the U16 final tournament.Objectives. Optimization of the physical preparation of 14–16 year old girls from the CSS basketball team. To update and improve the preparation programs for their future training lessons following the analysis of their physical development and physical capacity.Methods.The current study was conducted in two stages on 12 female basketball players. The first test was conducted in February 2023, in the competitive period before the U14 final tournament. The second test was conducted in February 2024, before the U15 final tournament. Prior to the study the athletes and parents completed consent statements for participation in the process of this study.Results. Indicators for physical development at the first test are stable, with the weight index being the most variable. The group is relatively homogeneous on specific indicators (20 m sprint run, vertical jump and Adapted T–Test. The greatest variation is in the Beep Test results, indicating that the group is inhomogeneous on this indicator.Conclusion. The analysis of the two tests shows that the basketball players obtained a better result in the second test, the applied training program had a positive effect on their physical training.The specific training program can be revised by increasing the workload and intensity of exercises
Keywords: basketball; physical training; training activity; control